Resíduos de equipamentos eletroeletrônicos: diagnóstico do descarte e manejo no município de Londrina (PR) - Ferreira, Leonardo Alves (2022)
The generation of waste electrical and electronic equipment (WEEE) has increased over the years and it is estimated that generation in the world will increase by at least 40% by 2030 (FORTI et al., 2020). With the advancement of technology, devices will become obsolete, so people need to dispose of them correctly. In 2020, rules were regulated for the implementation of mandatory reverse logistics (LR) of electrical and electronic products for domestic use in Brazil through Decree 10,240 (BRASIL, 2020a). This work aimed to diagnose the management of WEEE in the municipality of Londrina, identifying the voluntary delivery points (VEPs), the actions and campaigns carried out by the Municipal Secretariat for the Environment in addition to studying the flow of receipt and management of WEEE in a recyclable waste collection cooperative, at a work point for informal collectors and at a private WEEE collection entity. To meet the goals, visits were made to the sites and access to information on the websites of the managers and city hall. Based on the collected data, it can be concluded that the municipality has played an important role in the management of WEEE due to the presence of local private entities, RL management entities and several VEPs. In addition, Municipal Secretariat for the Environment develops environmental education actions and WEEE collection campaigns. On the other hand, situations to be improved were also identified since the VEPs installed are concentrated in the central area, making it difficult to serve the entire population of the municipality. As a suggestion, it is recommending a better evaluation for the installation of new VEPS, considering the population of each region and the intensification of awareness campaigns of the population for the correct destination of WEEE, promoting the circular economy.